The influence of attachment styles on student's self directed learning - Muhamad Suhaimi Taat; Mohd. Yusof Abdullah (International Interdisciplinary Journal of Scientific Research, 2014)
The main purpose of this research was to investigate the influence of attachment style on the self-directed learning (SDL) among secondary students in Malaysia. This quantitative survey research involved 407 form five students from the state of Sabah. This research used four types of Attachment Style developed by Bartholomew and Horowitz (1991), and Self Regulation in Learning (Borkowski & Dukewich, 1996), as the main platform for the research framework. Data was analysed using SmartPLS 2.0. The main finding demonstrated significant influence of exogenous variable which is attachment styles on the endogenous variable which is self-directed learning (SDL). The SEM analysis using SmartPLS showed that Secure style was the major influence on the student’s attachment style (factor loading=.883, p < 0.001). Moreover, attachment style contributed 15.6% towards student’s self-directed learning. It is hoped this research will be able to contribute valuable input for the enhancement of the national educational system.